Database of Wannier tight-binding Hamiltonians using high-throughput density functional theory - Kevin F. Garrity (Nature Portfolio, 2021)
Measurement(s) material property • electronic band structure Technology Type(s) computational modeling technique Factor Type(s) material Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14161406